Memahami Konsep Menyangkal Diri, Memikul Salib dan Mengikut Yesus: Sebuah Analisis Biblikal Lukas 9:23-26 - Danny Yonathan (Jurnal Teologi Berita Hidup, 2019)
From every generation, believers receive instruction that aims to strengthen faith and educate believers to become militant disciples of Christ, and have readiness to serve God in accordance with the true concept of Christian thought. Thus believers must dare to deny themselves, and carry the cross every day and follow Jesus Christ who is the Lord and Savior. This article had purpose to give the understanding biblically the concept of self-denying, carrying cross and following Jesus according to the text of Luke 9:23-26. AbstrakDari setiap generasi, orang percaya menerima pengajaran yang bertujuan untuk meneguhkan iman serta mendidik  orang-orang percaya untuk menjadi murid Kristus yang militan, serta memiliki kesiapan untuk melayani Tuhan sesuai dengan konsep pemikiran Kristen yang benar. Orang percaya harus mau menyangkal diri, dan memikul salib setiap hari serta mengikut Yesus Kristus yang adalah Tuhan dan Juruselamat. Artikel ini bertujuan untuk memberikan pemahaman secara biblikal konsep menyangkal diri, memikul salib dan mengikut Yesus sesuai dengan teks pada Lukas 9:23-26.